2014
DOI: 10.4103/1995-705x.132143
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of acute myocarditis with multiple intracardiac thrombi: The role of hypercoagulable states

Abstract: In acute myocarditis, thrombus formation is an important prognostic factor. Early diagnosis and treatment of intracardiac thrombus is critical, especially when there are multiple thrombi. When a patient presents with multiple cardiac thrombi not only cardiac disorders, but other diseases such as malignancies, rheumatologic disorders and thrombophilia must be considered in the differential diagnosis. Although the presence of hypercoagulable states does not generally affect the treatment choice, it may have an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…It is essential to consider homocysteinemia as an important differential diagnosis in patients with cardiac thrombosis. Left ventricular thrombus formation has also been reported in patients with normal left ventricular dimensions and systolic function due to hypercoagulable states such as raised homocysteine level (11). Studies have shown that increased levels of homocysteine are associated with increased risk of heart attack and stroke (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential to consider homocysteinemia as an important differential diagnosis in patients with cardiac thrombosis. Left ventricular thrombus formation has also been reported in patients with normal left ventricular dimensions and systolic function due to hypercoagulable states such as raised homocysteine level (11). Studies have shown that increased levels of homocysteine are associated with increased risk of heart attack and stroke (12).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of homocysteine are associated with low levels of vitamins B6, B12 and folate and also in chronic renal diseases (12). Hyperhomocysteinemia leads to endothelial cell damage, reduction in flexibility of vessels, and alters the process of hemostasis (11). It is suggested to perform thrombectomy in order to reduce cardiovascular risk along with proper anticoagulation and administration of vitamin B12, vitamin B6 and folate regardless of the levels before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Myocarditis is a hypercoagulable state induced by a systemic inflammatory process [7], and thus adequate anticoagulation therapy is required during VA-ECMO to prevent thrombotic complications. In particular, when SEC is observed in a patient with severe LV dysfunction, the risk of these complications increases.…”
Section: Dear Editormentioning
confidence: 99%
“…JACEP Open published by Wiley Periodicals LLC on behalf of American College of Emergency Physicians ity is a hypercoagulable state, there might be a clot and thrombosis of the heart and it can further result in acute myocarditis. 4 Rujittika Mungmunpuntipantip PhD 1 Viroj Wiwanitkit MD 2 1 Private Academic Consultant, Bangkok, Thailand 2 DY Patil University, Pune, India…”
mentioning
confidence: 99%